2015
DOI: 10.1038/srep17339
|View full text |Cite
|
Sign up to set email alerts
|

Noise-assisted energy transport in electrical oscillator networks with off-diagonal dynamical disorder

Abstract: Noise is generally thought as detrimental for energy transport in coupled oscillator networks. However, it has been shown that for certain coherently evolving systems, the presence of noise can enhance, somehow unexpectedly, their transport efficiency; a phenomenon called environment-assisted quantum transport (ENAQT) or dephasing-assisted transport. Here, we report on the experimental observation of such effect in a network of coupled electrical oscillators. We demonstrate that by introducing stochastic fluct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 27 publications
2
49
0
Order By: Relevance
“…In its simplest configuration, reduced-OQS subject to Born-Markov premises can be investigated in finite quantum networks in which environmental effects are modeled by introducing pure dephasing or, more generally, non-dissipative noise, into the site energies [10]. At the single particle level, the relevance of such dephasing models have been highlighted in an interdisciplinary framework of studies ranging from biology [11,12], via quantum chemistry [13,14], and electronics [15] to photonics [16] and ultra-cold atoms [17]. As it turns out, single-particle dephasing models do not show any divergence from wave mechanics [10,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In its simplest configuration, reduced-OQS subject to Born-Markov premises can be investigated in finite quantum networks in which environmental effects are modeled by introducing pure dephasing or, more generally, non-dissipative noise, into the site energies [10]. At the single particle level, the relevance of such dephasing models have been highlighted in an interdisciplinary framework of studies ranging from biology [11,12], via quantum chemistry [13,14], and electronics [15] to photonics [16] and ultra-cold atoms [17]. As it turns out, single-particle dephasing models do not show any divergence from wave mechanics [10,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…To elucidate the effect of the stochastic coupling between sites, we now compute the dynamics of a single excitation in a fully connected network composed by three sites. We have chosen this configuration, because it constitutes the simplest quantum network that one can investigate both theoretically and experimentally [5,24]. The energies of the sites are arbitrarily chosen to be ω 1 =ω 2 =ω 3 =5 ps −1 , whereas the coupling between them are set to κ 12 =1 ps −1 , and κ 13 =κ 23 =0.5 ps −1 .…”
Section: Single-particle Dynamicsmentioning
confidence: 99%
“…The study of quantum random walks in noisy environments have played a fundamental role in understanding non-trivial quantum phenomena observed in an interdisciplinary framework of studies ranging from biology [1,2], chemistry [3], materials science [4] and electronics [5], to photonics [6][7][8][9] and ultracold matter [10,11]. For many years, most of the research efforts had been focused on the propagation of single particles [12]; however, a great interest in describing the dynamics of correlated particles in noisy systems has recently arisen [13][14][15][16], mainly because it has been recognized that many-particle quantum correlations can be preserved in noisy networks by properly controlling the initial state of the particles, their statistics, indistinguishability or their type of interaction [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Besides theoretical studies, ENAQT has been reported in experiments with superconducting quantum circuits [34], photonic setups [35], classical oscillators [36] and trapped-ions [37]. All these works show that in certain parameter regimes the efficiency of the energy transfer is enhanced by environmental noise.…”
Section: Introductionmentioning
confidence: 99%